Antifeedant Constituents from Leucaena leucocephala - Poonam Negi, Bhupendra Singh Rawat, Devendra Singh Negi (Journal of Applied Pharmaceutical Science, 2016)
Hexane and methanolic extracts of Leuceana leucocephala Lam. leaves were tested against Spodoptera litura L. a polyphagus pest of cotton rice, tomato, ground nut, castor and legume and found to have antifeedant potential in the concentration of 2.5 μg/cm2. The bioassay-guided fractionation yielded the three compounds quercetin 3-O-rhamnoside (1), quercetin (2) and D-onanitol, (3) with antifeedant activity.
Keywords: Leucaena leucocephala, Mimosaceae, Spodoptera litura, quercetin 3-O-¬ rhamnoside.